Strategi Pembelajaran Bahasa Arab dengan Menggunakan Model Pembelajaran Window Shoping di Jurusan PBA UIN Mataram - Alirsyadi, Rifki; Saputra, Muhazzan; Mardiana, Ika; Hermawati, Aulia; Suparmanto, Suparmanto (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
The strategy in learning is very important and the method used will greatly affect the improvement of learning. As we know, giving or presenting a method in learning is not easy because there are still many teachers who present learning with inappropriate methods so that students feel bored and not interested in learning and listening to the teacher's explanation. Based on this, the researcher offers a learning method that is expected to help improve learning, namely a learning method using window shopping which aims to increase children's interest and creativity. The method used in this study is a qualitative description with the data collection instrument, namely observation. And examined by looking at references from previous journals and books or called literature studies. The results of this study indicate that using the window shopping learning method can help increase a child's creativity and critical thinking skills and interest in learning.